Analisis Hukum Terhadap Pemutusan Hubungan Kerja (PHK) di Hotel Maqna Gorontalo (Jurnal Begawan Hukum (JBH), 2024)
The purpose of this research is to find out the provisions regarding Termination of Employment Relations (PHK) in Law No. 13 of 2003 concerning Employment, and to find out the Settlement of Termination of Employment Relations (PHK) by the Maqna Gorontalo Hotel. The method used in this research is an empirical method. The research results found provisions regarding Termination of Employment Relations (PHK) in Law No. 13 of 2003 concerning Employment. There are layoffs by law which consist of, the work contract expires, failure to pass the probationary period and death, then there are layoffs by workers, namely resignation, urgent reasons, retirement, then finally layoffs by employers which consist of minor worker/labor mistakes, errors. heavy workers/labourers, Company closed for bankruptcy, force majeure, efficiency, Change of status, property, location, worker refuses, Change of status, property, location, entrepreneur/employer refuses, Worker/laborer with prolonged illness experiences disability due to work accident. Then the Settlement of Termination of Employment Relations (PHK) by Hotel Maqna Gorontalo has gone through various processes from internal to the mall, kinship, mediation to court, at the Industrial Relations Court with case number 36/Pdt.Sus-PHI/2021/PN Gto ending with the Company winning because the lawsuit was an error in person/wrong person being sued. It is also based on information from the employment party that the Company is not at fault but these employees do not accept that they were not called to another Company status.